Objective Structured Clinical Examination (OSCE) Station on Communicating Poor Prognosis to the Family in a Neurological Acute Care Setting - Penelope Smyth; Valerie Sim (Association of American Medical Colleges, 2014)
Abstract Introduction Stroke is a common cause of patient morbidity and mortality. Communicating its prognosis to family members, along with the establishment of goals of care, is a frequent task for neurologists and neurology residents. Given this, we felt it was an appropriate scenario from which to assess neurology resident medical expert and communication skills in an objective structured clinical examination (OSCE) setting. The OSCE station topic was created directly from objectives of training for neurology residents specified by the Royal College of Physicians and Surgeons of Canada. Methods This is a standardized case with an actor portraying a patient's relative. Residents are to give bad news of poor neurologic prognosis and establish goals of care for the patient. The case scenario, instructions to the examinee, and examiner marking sheet are included. Results The OSCE station was implemented with pediatric and adult senior neurology residents (PGY3-PGY5) from three universities. Of the 25 residents who experienced this case, 96% passed the station. Resident scores ranged from 60%-100%, with a mean of 86%. Discussion We consider the significance of the work to be the interpretation of a clinical scenario of poor neurologic prognosis of severe stroke and the communication of poor prognosis to a standardized family member with resultant establishment of code status, a task that is performed several times per week on the acute stroke service. This OSCE station is appropriate for neurology residents who participate in stroke care and will become neurologists who must communicate bad news on a daily basis.